Strategi Pengembangan Bahan Ajar Pendidikan Agama Islam - Muqoffi Muqoffi; Sulalah Sulalah; Muhammad Walid (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2023)
Many educational programs concentrate on maturing learning models, strategies and approaches, while the content of the material is not a serious concern, so it is not something that is an anomaly if Islamic religious education teaching materials in schools/madrasas find some errors. Therefore, the material for the development of teaching materials is absolutely necessary. The results of the study concluded that the strategy for developing teaching materials was carried out in 5 hierarchical stages, namely: 1. Identification of needs. Characterized by the lack of teaching materials to achieve teaching goals. 2. Looking for curriculum materials. The way it works is to find and classify materials related to the needs of the institution. 3. Analysis of curriculum materials. It is an activity of separating various materials into small parts and then testing each part and whether they are related to one another or not. 4. Assessment of curriculum materials. This is done in two ways, namely checking the completeness of the material and reading critical reviews or reports from evaluation studies. 5. Making decisions on the adoption of curriculum materials. This is done by registering the teaching materials used that are deemed less relevant to the needs and conducting research that aims to select and assess the new teaching materials that have been obtained.